Effectiveness of Intravenous Immunoglobulin Therapy for Pediatric Viral Encephalitis - Ji Eun Byun; Kyung Yeon Lee (Korean Child Neurology Society, 2020)
Purpose Intravenous immunoglobulin (IVIg) is considered as a first-line therapy for autoimmune encephalitis. However, its effectiveness in viral encephalitis has yet to be evaluated. Therefore, we investigated the effectiveness of IVIg therapy for pediatric viral encephalitis. Methods We retrospectively reviewed the records of 35 pediatric patients who were hospitalized with confirmed or suspected viral encephalitis. Twenty patients (57.1%) were treated with IVIg in conjunction with conventional therapy (IVIg-treated group), and 15 patients (42.9%) were treated with conventional therapy (non-IVIg-treated group). We compared the clinical characteristics of the groups at admission and their clinical outcomes. Results Compared to the non-IVIg-treated group, the IVIg-treated group had more critical clinical features at admission, with a lower score on the pediatric Glasgow Coma Scale (mean±standard deviation, 9.1±2.3 vs. 10.8±2.7, P=0.025), longer fever duration (3.5±2.2 days vs. 1.8±1.1 days, P=0.022), and higher incidence of magnetic resonance imaging abnormalities (14/19 [73.7%] vs. 3/15 [20.0%], P=0.002). Nevertheless, the clinical outcomes of the IVIg-treated group were comparable to those of the non-IVIg-treated group in terms of mortality rate (1/20 [5.0%] vs. 0/15 [0%]), neurological deficits at discharge (2/20 [10.0%] vs. 1/15 [6.7%]), and occurrence of epilepsy (5/20 [25.0%] vs. 2/15 [13.3%]). Fourteen (70.0%) and 13 (85.7%) patients in the IVIg-treated and the non-IVIg-treated groups, respectively, achieved complete recovery without any neurological complications. Conclusion IVIg may be considered as a potential immunomodulating agent when treating critical pediatric viral encephalitis to improve neuropsychological outcomes.